The Performance Of Steam Engine System With Retrofitted Reciprocating Engines - Zainal Abiden, Zabeer Abhar (Universiti Sains Malaysia, 2018)
Steam engines were one of the early human inventions in power generation technology. They were essential during the Industrial revolution as steam engines are used in ships, locomotives and also factories in driving machineries. At present, there are no available steam engines in the market and it is usually self-developed by using any engines that are available. This project is done to determine the performance of two engines that are available in a steam engine system. The steam engine system is composed of 3 main parts which are the boiler, pressure regulating valve and the steam engine. The boiler which is fueled by LPG is a vertical fire-tube boiler with a 7.5 liter capacity and can operate up to 10 bar of pressure. The pressure regulating valve is a Yoshitake GD-45P which has maximum operating temperature of 220℃ and maximum operating pressure of 2MPa. The steam engines are a 2-stroke engine and a 4-stroke converted 2-stroke engine. The performance of the steam engine system was determined at three different speeds of flywheel by the variation of load and inlet pressure where the speed of the flywheel is maintained. The boiler has the efficiency of 44.68% and can supply power input to the engine up to 5kW. Due to low efficiency and power generated by the boiler, the 4-stroke engine is not suitable to operate in this system. However, for the 2-stroke engine, the highest brake power, indicated power and friction power is 4.01 W, 5.408 kW and 5.405 kW respectively. The highest specific steam consumption is 4075.09 kg/kWh. Besides, the highest mechanical efficiency is 0.127% while the highest specific steam consumption is 4075.09 kg/kWh. A quite low overall efficiency is obtained for the 2-stroke engine in this system which is 0.0523%.